Effects of ibuprofen and microplastics on movement, growth and reproduction in the freshwater snail Physella acuta - Elías, Daniel; Ramirez Vieytez, Jazmin; Funoy Sayar, Morena; Loaisiga, Jorge; Harper, Ayden; Doll, Jason (Frontiers in Environmental Science, 2025)
Emerging contaminants such as microplastics and pharmaceuticals in freshwater ecosystems are a growing concern, seriously affecting aquatic organisms. Ibuprofen, a widely used anti-inflammatory drug, is commonly found in rivers, streams, and water systems where it is discharged. As a result, organisms that inhabit these environments, such as snails, are affected in their natural habitats. This study examines the effects of microplastics (10 μg/L), ibuprofen (500 μg/L), and a combination of ibuprofen (500 μg/L) and microplastics (10 μg/L) on growth, movement, and reproduction in Physella acuta, a freshwater snail species. While no significant effects were observed on movement or number of egg clusters, there was a significant decrease in growth when snails were exposed to microplastics or the combination of microplastics and ibuprofen (p = 0.021). Additionally, snail egg production decreased when exposed to ibuprofen (p = 0.001) but increased when exposed to microplastics (p = 0.002). Microplastic exposure produced more eggs than ibuprofen (p < 0.001) and ibuprofen and microplastics combined (p < 0.001). Our results suggest that ibuprofen affects growth and the total number of eggs, likely due to oxidative stress, neurotoxicity, or disrupted hormonal pathways. In contrast, microplastics may have caused digestive system blockage, thus affecting energy allocation for growth and reproduction. Changes in snail fitness can directly and indirectly affect food webs and nutrient cycles, highlighting the need for research on these pollutants to understand their chronic and long-term effects on ecosystems.